2008
DOI: 10.1161/hypertensionaha.108.111559
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Type Plasminogen Activator Release in Healthy Subjects and Hypertensive Patients

Abstract: Abstract-The relationship between adrenergic stimuli and NO in modulating tissue-type plasminogen activator (t-PA) release from endothelial cells was investigated in normotensive subjects and essential hypertensive patients. Sympathetic activation, a well-known stimulus for endogenous fibrinolysis, is also involved in the determination of cardiovascular risk in essential hypertension. However, the existence of cross-talk between adrenergic stimuli and NO availability in modulating t-PA release is not well es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In addition, bradykinin-mediated tPA release was found to be sensitive to L-NMMA, which indicates a positive modulatory effect of the NO pathway in physiological conditions, a finding in line with previous reports of application of different endothelial stimuli, such as substance P or epinephrine. 3,26 The positive role of the NO pathway was further confirmed by the finding that acetylcholine-induced tPA release was significantly blunted by NO inhibition in normotensive subjects. 4 In normotensive subjects, sulfaphenazole also significantly reduced bradykinin-induced tPA release, a finding that suggests that a CYP 2C9 -dependent pathway could be physiologically able to participate in fibrinolysis modulation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, bradykinin-mediated tPA release was found to be sensitive to L-NMMA, which indicates a positive modulatory effect of the NO pathway in physiological conditions, a finding in line with previous reports of application of different endothelial stimuli, such as substance P or epinephrine. 3,26 The positive role of the NO pathway was further confirmed by the finding that acetylcholine-induced tPA release was significantly blunted by NO inhibition in normotensive subjects. 4 In normotensive subjects, sulfaphenazole also significantly reduced bradykinin-induced tPA release, a finding that suggests that a CYP 2C9 -dependent pathway could be physiologically able to participate in fibrinolysis modulation.…”
Section: Discussionmentioning
confidence: 81%
“…26 It is, however, interesting to observe that in hypertensive patients, the residual but still evident bradykinin-induced tPA release was totally resistant to L-NMMA, whereas it was blocked by sulfaphenazole. Finally, when L-NMMA was coinfused with sulfaphenazole, no further reduction in tPA release was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in humans, impaired capacity of the endothelium to release t‐PA has been linked to atheromatous plaque development and higher rates of myocardial infarction 29. We4 and others30 have previously demonstrated that endothelial t‐PA release is markedly blunted in adults with elevated BP and that the magnitude of impairment is similar between adults with prehypertension and stage 1 hypertension 4. Impaired endothelial fibrinolytic function is considered to be an important factor contributing to the increased risk of atherothrombotic vascular disease associated with elevated BP 31…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known regarding the effects of BP‐lowering agents on endothelial control of the fibrinolytic system 30, 32. While acutely lowering BP in adults with hypertension does not have beneficial effects on endothelial t‐PA release,33 chronic BP control with angiotensin‐converting enzyme inhibition or calcium channel blockade,8 but not angiotensin receptor blockade,7 improves arterial t‐PA release 31.…”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, the systemic levels of t-PA may not reflect the local profibrinolytic capacity in terms of availability of active t-PA at the organ level, which in turn depends on the magnitude of local t-PA release from the endothelium. 24,25 Data on the effects of Ang II AT1 receptor blockers (ARBs) on fibrinolysis are even more controversial, with some studies showing a reduction in PAI-1 plasma level [26][27][28] and others showing no effect. 19,[29][30][31][32] Reasons for such different findings might be because of differences in experimental models, study population characteristics, duration of treatment and possible methodological bias.…”
Section: Introductionmentioning
confidence: 99%